2005
DOI: 10.1073/pnas.0507808102
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococcus produce pilus-like structures containing protective antigens and Lancefield T antigens

Abstract: Although pili have long been recognized in Gram-negative pathogens as important virulence factors involved in adhesion and invasion, very little is known about extended surface organelles in Gram-positive pathogens. Here we report that Group A Streptococcus (GAS), a Gram-positive human-specific pathogen that causes pharyngitis, impetigo, invasive disease, necrotizing fasciitis, and autoimmune sequelae has long, surface-exposed, pilus-like structures composed of members of a family of extracellular matrix-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
393
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 330 publications
(404 citation statements)
references
References 23 publications
9
393
1
1
Order By: Relevance
“…These pili, which are extremely thin (2-5 nm in diameter) but can extend up to 4 m from the bacterial cell surface (4), are formed as covalently linked polymers through the action of cysteine transpeptidase enzymes called sortases. In this process, which is common to a number of Gram-positive bacterial pathogens, the pilus backbone is formed from a single protein subunit, the so-called major pilin, by the covalent, endto-end polymerization of major pilin subunits, generating an assembly resembling beads on a string (5)(6)(7).…”
mentioning
confidence: 99%
“…These pili, which are extremely thin (2-5 nm in diameter) but can extend up to 4 m from the bacterial cell surface (4), are formed as covalently linked polymers through the action of cysteine transpeptidase enzymes called sortases. In this process, which is common to a number of Gram-positive bacterial pathogens, the pilus backbone is formed from a single protein subunit, the so-called major pilin, by the covalent, endto-end polymerization of major pilin subunits, generating an assembly resembling beads on a string (5)(6)(7).…”
mentioning
confidence: 99%
“…Pili, long filamentous protein structures that extend from bacterial surfaces 24 , form by covalent polymerization of subunits catalysed by an enzyme called sortase [25][26][27] . As pilus subunits are arranged head-to-tail, pili are thin (2-5 nm).…”
mentioning
confidence: 99%
“…Interestingly, three of these proteins were found to assemble into pili. Based on these pioneering findings, a search for molecular signatures for typical pilus regions was also applied by Mora et al [64] in a comparative reverse vaccinology study aimed to identify S. pyogenes vaccine candidates. Genome sequence analysis of five different circulating strains suggested that a multicomponent vaccine combining 12 backbone variants of pilus protein genes might provide protection against over 90% of circulating strains of S. pyogenes.…”
Section: Reverse Vaccinology and The Promise For Next-generation Vaccmentioning
confidence: 99%